Friedrich Hebbel's Conception of Movement in the Absolute and in History - Flygt, Sten G. (UNC Studies in the Germanic Languages and Literatures, 1952)
Flygt undertakes an analysis first of Hebbel's writings on social and historical progress in his letters and diaries and then of his plays, in order to draw conclusions on Hebbel's conception of movement. Noting oscillations throughout Hebbel's life between social progressivism and conservatism, Flygt turns his focus to the Hebbel's conceptions of flux and change both in society and the individual.